Girls, Maids or Young Women? Notes for an Analysis Of Childhood in the Late Colonial Period (Rio De La Plata, 18th and 19th Centuries) - Sidy, Bettina (Revista de Historia Social y de las Mentalidades, 2024)
This paper explores how minors were consigned during the late colonial period in the Río de la Plata region. We focus on an operational segmentation of female childhood minorities from this period, addressing their legal characterisation and the ambiguities surrounding its delineation. Our analysis is based on a set of judicial processes structured around two key elements concerning the treatment of minors: their involvement in service tasks and their identification as maids, and the issue of sexuality, particularly how society responded to the violence inflicted upon them.
Keywords: Childhood; Gender; Colonial Society; Justice